Comparative Analysis of the Influence of Building Vibration on Human Comfort Caused by Blasting and Subway Train Loads. Issue 1 (February 2020) - Xiong, Yilei; Zhang, Shenglong; Wu, Zongzhen; Wang, Wenbin; An, Zilong; Wei, Zhiheng
Abstract: In order to compare the difference between impact of the building vibration on human comfort caused by blasting and subway train load, the finite element model is established and two kinds of excitations are applied to analyze and evaluate the dynamic response of building structure under two working conditions. The research results show that the building vibration caused by train load has a long duration and relatively low vibration amplitude; the building vibration caused by blasting load has a short duration and relatively high vibration amplitude. Both vibrational energies exceed the standard limits and have adverse effects on residents from the perspective of sustainability and impact.